MENINGKATKAN MUTU MASYARAKAT MELALUI PEMAHAMAN KULTUR SEKOLAH - ABHANDA AMRA (Ta'dib, 2010)
Ethnic diversity in the forms language, values way of life is the greatest gift from the Almighty God to Indonesian people. However, horizontal conflicts, such as among ethnic groups, religions, and the like, leave a big question: Does education fail to build and develop senses of humanity, brotherhood and unity? This implies that the application of present educational system has not yet successfully builds tough characters and develops creative ideas to solve problems concerning with economic crises. Furthermore, moral crises – slaughters, rapes, brawls, and the like – takes place everywhere. Dealing with moral crises, there are three big issues that can be proposed: 1) how schools reconstruct society to be more survived in the global era, 2) what types of education to strengthen our educational system, and 3) what are the chances of art education to unite and build character of nation.Kata kunci: mutu, pemahaman, sekolah